Pengaruh Digital Marketing, Brand Image, dan Inovasi Produk Terhadap Repurchase Intention Produk Skincare Somethinc Pada Mahasiswa Di Kota Malang - Halimah, Istik Noor; Basalamah, Muhammad Ridwan; Arsyianto, Muhammad Tody (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the effect of Digital Marketing, Brand Image, and Product Innovation on Repurchase Intention on Somethinc skincare products among Malang City students. The study used a quantitative approach with a sample of 85 respondents from the Islamic University of Malang (UNISMA), State University of Malang (UM), and Brawijaya University (UB). The selection of respondents was based on ease of access, efficiency of questionnaire distribution, and affordability of researchers as active students of UNISMA. Data collection was conducted through an online questionnaire using Google Form, and analyzed using SPSS version 27. The results showed that Digital Marketing has no significant effect on repurchase intention, while Brand Image and Product Innovation have a positive and significant effect on repurchase intention.